1981
DOI: 10.2307/1937282
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Mass in Breeding Wrens: Stress or Adaptation?

Abstract: Losses of mass in breeding passerines are commonly observed and presumed to reflect physiological stress from activity while feeding nestlings. Analyses of changes of body mass in House Wrens (Troglodytes aedon) show that: (1) females lose ° 13% of their body mass between onset of incubation and fledging, but reattain their original mass for second broods; (2) 50% of mass loss is achieved before hatching is completed; (3) loss of mass is virtually complete before food demands of the nestlings are greatest; (4)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
143
1
3

Year Published

1996
1996
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(156 citation statements)
references
References 22 publications
(15 reference statements)
9
143
1
3
Order By: Relevance
“…This change is traditionally interpreted as either a sign of stress (Ricklefs 1974;Nur 1984) or an adaptation to increase flight efficiency during a demanding period of brood rearing (Freed 1981;Norberg 1981;Houston 1993;Hillström 1995). Our model raises the possibility of a novel explanation for this mass loss; the parents lose mass to manipulate their mate's behavior.…”
Section: Discussionmentioning
confidence: 89%
“…This change is traditionally interpreted as either a sign of stress (Ricklefs 1974;Nur 1984) or an adaptation to increase flight efficiency during a demanding period of brood rearing (Freed 1981;Norberg 1981;Houston 1993;Hillström 1995). Our model raises the possibility of a novel explanation for this mass loss; the parents lose mass to manipulate their mate's behavior.…”
Section: Discussionmentioning
confidence: 89%
“…Mass loss during incubation has been interpreted as an adaptive response to increase foraging efficiency by reducing flight costs or as a consequence of physiological stress. [21][22][23][24] If mass decrease in Common Terns is an adaptive strategy, it should occur in any year. In this study, however, the change in body mass of incubating females differed between years.…”
Section: Incubationmentioning
confidence: 99%
“…In birds, body mass loss has been considered a strategy to reduce maintenance cost during energy-costly activities such as reproduction (Freed, 1981;Norberg, 1981;Cavitt and Thomson, 1997;Bech et al, 2002), locomotion (Deerenberg et al, 1998;Elliott et al, 2008) and moulting (Portugal et al, 2007). Several studies have reported body mass losses in different species of aquatic birds during the adjustment period to saltwater (e.g.…”
Section: Introductionmentioning
confidence: 99%